2009
DOI: 10.1097/ta.0b013e31819ea61a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Complement Component 2 of the Classical Complement Pathway is Associated With Increased Mortality and Infection: A Study of 627 Patients With Trauma

Abstract: Trauma is a disease of inflammation. Complement Component 2 (C2) is a protease involved in activation of complement through the classical pathway and has been implicated in a variety of chronic inflammatory diseases. We hypothesized that genetic variation in C2 (E318D) identifies a high-risk subgroup of trauma patients reflecting increased mortality and infection (Ventilator associated pneumonia: VAP). Consequently, genetic variation in C2 may stratify patient risk and illuminate underlying mechanisms for ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…C2 is part of the membrane attack unit of complement C4b2a3b that causes cell lysis. Its antiinfective role is supported by a previous observation that carriers of the same mutation have higher mortality rates and more complications of infection 20. Our study is the first to show an association of this variant with CHB, suggesting that an unimpaired complement system may play an important, although as yet unexplained, role in anti‐CHB infection.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…C2 is part of the membrane attack unit of complement C4b2a3b that causes cell lysis. Its antiinfective role is supported by a previous observation that carriers of the same mutation have higher mortality rates and more complications of infection 20. Our study is the first to show an association of this variant with CHB, suggesting that an unimpaired complement system may play an important, although as yet unexplained, role in anti‐CHB infection.…”
Section: Discussionsupporting
confidence: 82%
“…The TMEM2 variant p.Ser1254Asn was entered in the dbSNP133 during our investigation with no indication of its immunological function. C2 p.Glu318Asp is reported in the literature, 20 but not with regard to HBV infection.…”
Section: Discussionmentioning
confidence: 89%
“…An in vitro model of myocardial ischemia (4) indicated that the infarct size was least in hearts from BN, whereas hearts from SS rats demonstrated the most adverse consequences of ischemia. Finally, data from trauma patients have demonstrated that differences in single nucleotide polymorphisms in mitochondrial DNA (9), complement (31), and ␤ 2 -adrenergic receptors (32) are associated with differences in mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Such investigations indicate that specific polymorphisms associated with mitochondrial Complex 1 [65] and complement component 2 [66] may be associated with increased mortality of trauma victims. Alternatively, a polymorphism in a β-2 adrenergic receptor (ADBR2: Q27E) was associated with enhanced survival after various blunt and penetrating injuries [67].…”
Section: A Physiogenomic Approachmentioning
confidence: 99%